The Effects Of Differing Density Of Swim-Training Sessions On Shoulder Range Of Motion and Isometric Force Production In National and University Level Swimmers - Matias Yoma; Lee Herrington; Tanya Mackenzie (International Journal of Sports Physical Therapy)
# Background